STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP PELAYANAN PUBLIK DI MASA NORMAL BARU COVID-19 OLEH APARATUR DESA MULYA SUBUR KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Yuningsih Yuningsih; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the problems in the implementation ofpublic services, which are still lacking, especially in the research location, namely thevillage of Mulya Subur, which is still complained about by the community starting fromhealth facilities, services for the convoluted public correspondence needs which areincreasing with the existence of limitation of activity during the new normal period ofCovid-19. The formulation of the problem in this study is how the public's perception ofpublic services in the new normal period of Covid-19 by the Village Apparatus MulyaSubur, Pangkalan Lesung District, Pelalawan Regency. The purpose of this study wasto determine how the public's perception of public services in the new normal period ofCovid-19 by the Village Apparatus Mulya Subur, Pangkalan Lesung District,Pelalawan Regency. The method used is descriptive quantitative, data collectioninstruments used in this study were questionnaires and interviews. The population inthis study were the people of Mulya Subur village. The sample in this study was taken byincidental sampling and quota sampling , amounting to 93 people. Based on the resultsof the research conducted, it can be concluded that the public's perception of publicservices in the new normal period of covid-19 by the Mulya Subur Village Apparatus,Pangkalan Lesung District, Pelalawan Regency is in the